2012
DOI: 10.2355/isijinternational.52.804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foamy Slag Height on Hot Spots Formation inside the Electric Arc Furnace Based on a Radiation Model

Abstract: Recent Electric Arc Furnaces are equipped with ultra high power transformers to provide maximum values of electric power and minimize the melting time. The active power is increased by increasing arc length and arc voltage, however in these conditions energy losses due to radiation can also be increased with a consequent decrease in thermal efficiency. The energy radiated from the electric arcs is transferred to the walls inside the EAF promoting hot spots which represent a catastrophic operational condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 4 publications
0
54
0
1
Order By: Relevance
“…By computational fluid dynamics modeling of AC electric arcs, it was found that to increase the efficiency in the power delivered to the arc; the arc length should be increased. 7) It is well known, from arc furnace physics theory and confirmed for many EAF operation experiences that lengthening the arcs increases arc radiation.…”
Section: Arc Power Under Unstable Arc Conditionsmentioning
confidence: 94%
See 2 more Smart Citations
“…By computational fluid dynamics modeling of AC electric arcs, it was found that to increase the efficiency in the power delivered to the arc; the arc length should be increased. 7) It is well known, from arc furnace physics theory and confirmed for many EAF operation experiences that lengthening the arcs increases arc radiation.…”
Section: Arc Power Under Unstable Arc Conditionsmentioning
confidence: 94%
“…According to computational fluid dynamics (CFD) simulations, 7) the power dissipated by AC electric arc is transferred by three different mechanisms: by convection , by radiation and by the electrons flow . Energy transferred by convection accounts for 70%, while the energy transferred by radiation is around 24% and the energy transferred by the flow of electrons, , represents only about 3% of the total energy transferred from the arc.…”
Section: Arc Thermal Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Arc stability is estimated by measuring harmonic content of the transformer's secondary side voltage or line current. Notice that the stability concept, referred in this article, is neither the plasma arc stability as defined in, 6,14) nor the stability of the electric power system, but it may have some relation with both of them. The electrical arc voltage can be modeled, in spite of its non-linearity, as a sum of harmonic voltages according with Fourier analysis.…”
Section: Harmonics and Thd As Arc Stability Indexmentioning
confidence: 99%
“…Since electric arcs are the main source of energy in electric arc furnaces, the electric energy provided by them represents Many models have been developed to simulate electrical arcs among which the MHD model, 4,5) Cassie-Mayr model, 6) channel arc model (CAM) 7) could be mentioned as examples. MHD models are more comprehensive than other types and include calculation of arc velocity profile, pressure profile and temperature profile; 4) however, the flaw of such models is that their parameterization and implementation require a large number of experimental data. 6) On the other hand, Cassie-Mayr arc models are easier to parameterize and they could be integrated into broader EAF models; but, they are usually used to model low arc powers.…”
Section: Introductionmentioning
confidence: 99%